Exploration of endophytic fungi and their bioactive potential associated with Punica Granatum - Haque, S.A.M. Salman (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2022.